PEMANFAATAN INTERNET DALAM PENGEMBANGAN KONSEP IPS DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BERMAKNA - Roni Faslah (Jurnal Ilmiah Econosains, 2011)
ABSTRACT Information Communication Technology has a significant impact on learning. ICT as a tool can be fully utilized in the concept of learning. Moreover, if the concept of learning in abstract form. The Internet can be a tool to develop concepts and create meaningful social studies learning. Learning resources are acquired and managed by advances in technology it is possible for students to learn the concepts of social science to be meaningful (meaningful), because with photographic images, documentary, animated or information presented to be more complete and detailed that it easily understood by students. Complex process can be simplified, faster process can be slowed, slow process can be accelerated without reducing substances subject matter. ICT can bring real experience into the classroom without having the students leave the classroom, so the real experience is in addition to creating meaningful learning will also develop social skills.Keywords: ICT, internet, social studies, meaningful learning